Costs estimates and rentability of the guava culture {psidium guajava l. patuma cv.) in monte alto county, Sao Paulo state - Tarsitano, Maria A.A. [UNESP]; Brunhara, Rita C. [UNESP]; Bidoia, Adalberto L. [UNESP]; Araujo, Carlos A.M. [UNESP]; Correa, Luis S. [UNESP]; Bernardes, Elaine M. [UNESP] (My University, 1997)
This work intended to calculate the rentability of the guava culture Paluma cv. in Monte Alto region-SP, estimating the costs of the implantation, maintenance, production and the gross income of this culture in the first three years of cultivation. The production system utilized refers to the cultural treatments usually used in this culture in the region. The costs estimates were based on the total operational costs methodology used by the Agricultural Economics Institute (I.E.A.). The results obtained showed that the implantation and maintenance costs of the culture, in the two first years was Rs7.402,31/alqueire. Considering the possibility that in guava orchard, on irrigated conditions, reach in the fourthy year a productivity of 80t/alqueire and that the current price is Rs0,20/kg, it is possible to estimate the gross income around of Rs16.000,00/alqueire, resulting in a net income of Rs9.497,06/alqueire.
Keywords: Guava Paluma cv.; Production costs; Profitability